Development and Assessment of a Horizontally Integrated Biological Sciences Course Sequence for Pharmacy Education - Dirks-Naylor, Amie J. (Am J Pharm Educ, 2015)
Objective. To design and assess a horizontally integrated biological sciences course sequence and to determine its effectiveness in imparting the foundational science knowledge necessary to successfully progress through the pharmacy school curriculum and produce competent pharmacy school graduates. Design. A 2-semester course sequence integrated principles from several basic science disciplines: biochemistry, molecular biology, cellular biology, anatomy, physiology, and pathophysiology. Each is a 5-credit course taught 5 days per week, with 50-minute class periods. Assessment. Achievement of outcomes was determined with course examinations, student lecture, and an annual skills mastery assessment. The North American Pharmacist Licensure Examination (NAPLEX) results were used as an indicator of competency to practice pharmacy. Conclusion. Students achieved course objectives and program level outcomes. The biological sciences integrated course sequence was successful in providing students with foundational basic science knowledge required to progress through the pharmacy program and to pass the NAPLEX. The percentage of the school’s students who passed the NAPLEX was not statistically different from the national percentage.